2007
DOI: 10.1016/j.cellbi.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Replicative senescence, telomere shortening and cell proliferation rate in Gaddi goat's skin fibroblast cell line

Abstract: We assessed aging in continuous donor skin fibroblast cell line GGM5 up to the 25th passage by in vitro replicative senescence, telomere dynamics and chromosomal abnormalities. Cell proliferation rate increased from 0.84+/-0.26 (primary cells) to 1.20+/-0.17 (13-15 passage group) per day and reduced to 0.65+/-0.14 in 22-25 passages. Cell proliferation rate was reduced by 45.7% after 87.62 CPDs. Cell viability reduced from 100% to 97.4% up to the 25th passages. Frequency of beta gal(+) cells increased in succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…The fetal and AF-derived cells in buffaloes have already been found to express key pluripotency molecular markers Dev et al 2011). In this study in long term cultures cells were able to proliferate up to 75 days and their proliferation rate was more up to 10 passages then decreased later may be due to accumulations of more non-dividing cells, was confirmed by earlier study conducted by Gupta et al (2007) in continuous culture of goat fibroblasts cells.…”
Section: Discussionsupporting
confidence: 77%
“…The fetal and AF-derived cells in buffaloes have already been found to express key pluripotency molecular markers Dev et al 2011). In this study in long term cultures cells were able to proliferate up to 75 days and their proliferation rate was more up to 10 passages then decreased later may be due to accumulations of more non-dividing cells, was confirmed by earlier study conducted by Gupta et al (2007) in continuous culture of goat fibroblasts cells.…”
Section: Discussionsupporting
confidence: 77%
“…It has been reported that due to inherent limitations in the mechanics of DNA replication, telomeres shorten at each cell division, and in the absence of telomerase, when telomere shortening reaches a critical limit, cells are susceptible to chromosomal aberrations such as end-to-end fusion and aneuploidy. In such a situation, the cells cease to divide and reach replicative senescence [40]. Treatment with TRF, however, protected against telomere shortening in senescent HDFs with concomitant increased in telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of telomerase, when telomere shortening reaches a critical limit, cells are susceptible to chromosomal aberrations such as end-to-end fusion and aneuploidy. In such a situation, the cells cease to divide and reach replicative senescence 5,6. Telomere length may restrict the replicative potential of hemopoietic cells contributing to the decline in immune function with age 7.…”
Section: Introductionmentioning
confidence: 99%